2011
DOI: 10.1111/j.1558-5646.2011.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Rapid Cold-Hardening In ceratitis Capitata

Abstract: Rapid cold-hardening (RCH) is a unique form of phenotypic plasticity which confers survival advantages at low temperature. The fitness costs of RCH are generally poorly elucidated and are important to understanding the evolution of plastic physiology. This study examined whether RCH responses, induced by ecologically relevant diel temperature fluctuations, carry metabolic, survival, or fecundity costs. We predicted that potential costs in RCH would be manifested as differences in metabolic rate, fecundity, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 84 publications
5
40
0
Order By: Relevance
“…After 3 d of egglaying, parents were removed for density control of experimental flies. Offspring were sorted by sex and were allowed to age for 5-7 d (11,18). Three replicates of 10-20 flies were moved to empty vials to avoid the influence of the food on the freezing temperature of flies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 d of egglaying, parents were removed for density control of experimental flies. Offspring were sorted by sex and were allowed to age for 5-7 d (11,18). Three replicates of 10-20 flies were moved to empty vials to avoid the influence of the food on the freezing temperature of flies.…”
Section: Methodsmentioning
confidence: 99%
“…Much work has focused on the physiological mechanisms and the ecological implications of both DACC and RCH, particularly to cold (14)(15)(16)(17)(18)(19). Despite its ecological importance, the physiological and genetic mechanisms underlying RCH have been challenging to unravel using physiological, transcriptomic, or metabolomic techniques, particularly because the physiological responses are both fast and transient (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…It is important to understand the factors that determine its distribution and abundance and, in this regard, the ability of C. capitata to adjust to temperature variations has been recently investigated, showing a broad thermal tolerance (Nyamukondiwa and Terblanche, 2009;Nyamukondiwa et al, 2010;Weldon et al, 2011;Basson et al, 2012). Basson et al (2012) demonstrated that cold exposure reduced C. capitata survival, which suggests the possibility of a chill-dependent injury, although flies showed no metabolic or fecundity costs. Therefore, it would be interesting to investigate the effects that cold exposure produce in the physiological state of C. capitata individual flies within a population, and how this affects their survival and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, short-term ‘hardening’, involving a pre-exposure to sublethal high (heat shock) or low (cold shock) temperatures, have been shown to improve survival under subsequent more extreme temperatures [911]. Similar plastic responses can also be induced by longer pre-exposure times prior to exposure in extreme temperatures, referred to as acclimation [1215].…”
Section: Introductionmentioning
confidence: 99%